Corneal vesicles accumulate collagen VI associated with tissue remodeling in apolipoprotein a-I deficiency: a case report. Issue 1 (December 2017) - Namba, Hiroyuki; Narumi, Mari; Susa, Shinji; Ohe, Rintaro; Kato, Takeo; Yamakawa, Mitsunori; Yamashita, Hidetoshi
Abstract Background Apo A-I deficiency clinically shows low serum levels of HDL cholesterol and corneal opacity at a young age. Histopathological evaluations of affected corneas are not enough, and the mechanism of corneal opacity is still unclear. Case presentation A 61-year-old woman suffered from blurred vision with a corneal opacity. She had significantly reduced serum levels of high-density lipoprotein cholesterol and Apo A-I, stenosis of the coronary arteries, and ischemic heart failure. On genetic examination, a homozygous mutation of Apo A-ITsukuba was identified. Histopathological examination of the corneal button after PKP showed numerous vesicles in the corneal stroma, which were more prominent in the deep stroma than in the shallow stroma. Collagen VI was observed in some of those vesicles. Conclusion We experienced a rare case of corneal opacity due to Apo A-I deficiency. Our histopathological findings indicated that structural changes in corneal collagen fibrils contribute to the formation of stromal vesicles.